2021
DOI: 10.1088/1751-8121/abe426
|View full text |Cite
|
Sign up to set email alerts
|

The hidden symmetry of the asymmetric quantum Rabi model

Abstract: The asymmetric quantum Rabi model (AQRM) exhibits level crossings in the eigenspectrum for the values ϵ ∈ 1 2 Z o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 20 publications
0
66
0
Order By: Relevance
“…Here it should be mentioned that the word "hidden" is more used for asymmetric QRM with bias where the parity symmetry is generally broken in the model but there are certain points of bias strength that regain some symmetry. [67][68][69] Here our case is reverse in some sense, the parity symmetry is never broken either for the model or in the GS, but there is a symmetry breaking which is little noticed. Let us decompose the parity into two parts, P = P𝜎 Px where P𝜎 = 𝜎 x reverses the spin while Px = (−1) a † a effectively inverses the spatial space x → −x.…”
Section: Hidden Symmetry Breaking At Transition G 𝝀 Cmentioning
confidence: 99%
“…Here it should be mentioned that the word "hidden" is more used for asymmetric QRM with bias where the parity symmetry is generally broken in the model but there are certain points of bias strength that regain some symmetry. [67][68][69] Here our case is reverse in some sense, the parity symmetry is never broken either for the model or in the GS, but there is a symmetry breaking which is little noticed. Let us decompose the parity into two parts, P = P𝜎 Px where P𝜎 = 𝜎 x reverses the spin while Px = (−1) a † a effectively inverses the spatial space x → −x.…”
Section: Hidden Symmetry Breaking At Transition G 𝝀 Cmentioning
confidence: 99%
“…Since, for any qubit state, P 2 ≡< σ > 2 ≤ 1, the strong constraint (45) means that the only separable density matrix (41) of the two spins compatible with the emergence of a qutrit is the product of two homologous eigenstates of any spin component.…”
Section: Representation Of the Density Matrix In The Qutrit Subspacementioning
confidence: 99%
“…A similar route has recently been used to investigate the dynamics of a pair [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ] or a chain [ 32 , 33 ] of coupled spins (also greater than ) subjected to time-independent and time-dependent [ 34 , 35 , 36 ] external magnetic fields. Symmetry arguments have also been exploited to elegantly bring to light intriguing dynamic features of physical systems living in Hilbert spaces of infinite dimensions [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In Section 4 it is demonstrated that the time evolution of the two dipolarly coupled spins nests a qutrit subdynamics governed by a Hamiltonian model that is explicitly derived.…”
Section: Introductionmentioning
confidence: 99%
“…Among the generations, the asymmetric quantum Rabi model (A-QRM) has attracted much attention recently [42][43][44][45][46]. The A-QRM contains an extra driving term σ x compare to the standard QRM [29].…”
Section: Introductionmentioning
confidence: 99%
“…The interesting thing is that A-QRM seems to recover the symmetry at some certain values of [29,42,50,51]. Many scholars found that the A-QRM has a hidden symmetry [42][43][44][45]. More recently, an analysis of the energy spectrum of the A-QRM from a numerical point of view reveals that the hidden symmetry manifesting the energy level crossover happens for the driving amplitude equaling to an integer times half of the photon frequency ω [46].…”
Section: Introductionmentioning
confidence: 99%